Balloon and Glue Technique: A Modification of Distal Reinforcement to Prevent Anastomotic New Entry, Reducing Replacement Range in Acute Type A Aortic Dissection - Masato Furui; Go Kuwahara; Yuta Sukehiro; Hideichi Wada (Journal of Chest Surgery)
In emergency surgery for acute type A aortic dissection, the creation of needle holes can cause various issues and complications. One persistent challenge is the prevention of distal anastomotic new entry tears, which frequently necessitate additional intervention. Modification of the distal reinforcement technique offers a straightforward solution by combining existing hemostatic agents with tools such as occlusion balloons. We describe a modified distal reinforcement procedure employing a balloon-and-glue technique to help prevent new entry tears at the distal anastomosis and avoid total arch replacement. Ten patients with acute type A aortic dissection were treated using this technique. Postoperative computed tomography indicated no evidence of distal anastomotic entry tears. In conclusion, this modified distal reinforcement technique represents not only a method to prevent distal anastomotic new entry tears but also a palliative approach that may obviate the need for total arch replacement in patients in poor condition or of advanced age.